Severity of the Crisis and its Transmission Channels - Calderon, Cesar; Didier, Tatiana (World Bank, Washington, DC, 2012)
The current global crisis, although initially circumscribed to the US housing market, spread rapidly across markets and borders. It has affected almost all countries through different reinforcing channels: the contraction in international trade, capital flows, remittances, and international commodity prices. The main goal of this note is to empirically analyze the mechanisms through which the financial crisis of 2007-2009 propagated throughout the world by characterizing the main factors behind the fall in Gross Domestic Product (GDP) growth rates. The findings indicate that a greater decline in the growth rate was registered in countries with higher de facto trade openness, less resilient domestic financial markets, and, to a lesser extent, improved macroeconomic frameworks. To complement this evidence, we construct an aggregate index of the severity of the crisis that captures the real and financial consequences in each country of this unprecedented global financial shock.